CSS : the definitive guide : visual presentation for the web. - Meyer, Eric A., ....-; Weyl, Estelle, ....- (Beijing : O'Reilly, 2017)
If you're a web designer or app developer interested in sophisticated page styling, improved accessibility, and saving time and effort, this book is for you. This revised edition provides a comprehensive guide to CSS implementation, along with a thorough review of the latest CSS specifications. CSS is a constantly evolving language for describing the presentation of web content on screen, printers, speech synthesizers, screen readers, and chat windows. It is used by all browsers on all screen sizes on all types of IoT devices, including phones, computers, video games, televisions, watches, kiosks, and auto consoles. Authors Eric Meyer and Estelle Weyl show you how to improve user experience, speed development, avoid potential bugs, and add life and depth to your applications through layout, transitions and animations, borders, backgrounds, text properties, and many other tools and techniques. This guide covers: Selectors, specificity, and the cascade Values, units, fonts, and text properties Padding, borders, outlines, and margins Colors, backgrounds, and gradients Floats and positioning tricks Flexible box layout The new Grid layout system 2D and 3D transforms, transitions, and animation Filters, blending, clipping, and masking Media and feature queries
Includes index.
Previous edition: 2006.
Keywords: Cascading style sheets